Effect of Nearby Forest Fires on Ground Level Ozone Concentrations in Santiago, Chile - Lissi-Gervaso, E; Rubio-Campos, M; Gramsch-Labra, E (Multidisciplinary Digital Publishing Institute (MDPI), 2015)
On 4 and 8 January 2014, at the height of the austral summer, intense wildfires in forests and dry pastures occurred in the Melipilla sector, located about 70 km to the southwest of Santiago, the Chilean capital, affecting more than 6 million inhabitants. Low level winds transported the forest fire plume towards Santiago causing a striking decrease in visibility and a marked increase in the concentration of both primary (PM10 and CO) and secondary (Ozone) pollutants in the urban atmosphere. In particular, ozone maximum concentrations in the Santiago basin reached hourly averages well above 80 ppb, the national air quality standard. This ozone increase took place at the three sampling sites considered in the present study. These large values can be explained in terms of high NOx concentrations and NO2/NO ratios in biomass burning emissions. © 2015 by the authors.